A meta-analysis of the overall effect of mHealth physical activity interventions for weight loss and the moderating effect of behavioral change theories, techniques, and mobile technologies. (May 2022) - Qin, Yan; Wang, Xiaojing (Romy); Namkoong, Kang
Mobile technologies offer the potential for efficacious and cost-effective lifestyle interventions for weight loss. Extant research indicates that mobile health (mHealth) lifestyle interventions are potentially effective and practical methods of weight loss, but it is less known what intervention characteristics are associated with weight loss effects. This meta-analysis examined the effectiveness of mHealth physical activity interventions for weight loss compared with non-technology/usual care interventions and the moderating effects of behavioral change theories, techniques, and mobile technologies. A total of 24 studies were identified based on inclusion criteria. Weight loss was the primary outcome. The results showed a medium significant effect size ( d  = 0.395; 95% CI   = 0.243, 0.546; Z  = 5.107, p  < 0.001; N  = 5146) favoring mHealth interventions. Interventions were significantly more effective when wearable devices were used ( QB  = 4.102, df  = 1, p  < 0.05) and when feedback was employed ( QB  = 4.566, df  = 1, p  < 0.05). The implications for future mHealth intervention design are discussed.